Utilization of antenatal services in slum areas of Aligarh - Neyaz, Arslan; Sahu, Priyanka Chintaram; Ahmed, Malik Shanawaz (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Today, there are approximately 998 million slum dwellers in the world. As per census 2011, approximately 68 million Indians are living in slums. There have been limited efforts to capture the health of population living in urban slums and most severely affected are the women of childbearing age and children. Objective of this study was to assess the utilization pattern of antenatal care and to identify the factors affecting it among married women of reproductive age at two urban slum areas in Aligarh. Methods: A cross-sectional survey was carried out from July 2012 to June 2013 in two urban slums of Aligarh with sample of 405 women’s selected using systematic random sampling. IBM SPSS Statistics 17 was used for data entry and calculation of statistical tests like proportions, Chi square test. Results: Antenatal care (ANC) utilization was found to be 74.3%. 89.4% women received two doses of TT injections and 55.8% women consumed Iron Folic Acid (IFA) tablets at least for 90 days. Majority (72.4%) of the women utilized government facility for ANC check-up. Most common reason for not taking ANC was found to be tradition (34.6%). Woman’s education, husband’s education and occupation, birth order and socio-economic status of the family was found to be significantly associated (p <0.05) with utilization of antenatal care. Conclusions: Socio-demographic variables of reproductive age group women have impact on utilization of antenatal care services. Social and cultural accessibility is as important as physical accessibility. Important barriers to service utilization in this study include the tradition and economic constraints.